Makna Simbolik Aksesoris Pakaian Adat Pengantin Wanita Suku Dayak Kenyah Kalimantan Timur: Kajian Antropolinguistik - Puji Lestari, Dyah; Rahardi, R. Kunjana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The writing of this article aims to describe the meaning of the symbol of traditional bridal clothing and the function of traditional bridal clothing of the Dayak Kenyah tribe in East Kalimantan. The formulation of this research problem is how to group the meaning of symbols in traditional wedding clothing accessories of the Dayak Kenyah tribe and what are the functions of traditional bridal clothing accessories in the life of the Dayak Kenyah tribe in East Kalimantan. The research method used in this study is an ethnographic method with simplification of steps according to research needs. Data collection and data analysis methods in the form of interviews and literature studies. The results of the study show that there is a symbolic meaning found in the traditional wedding dress accessories of the Dayak Kenyah tribe.